Learning in Multicultural Environments: Learners as Co-designers - Zurita, Laura (Proceedings of the International Conference on Networked Learning, 2006)
This article will analyze how the teacher should collaborate with the learners in a co-design of virtual learning environments. Teachers design learning environments to fulfil a set of goals and aims, with a target group in mind. However, if there is a mismatch between the target group and the course, the learners will react to it either by exercising resistance, or by trying to adapt the artefact to their needs. In such cases, the teacher can use the learners’ contribution as an input to the design. By using cultural historical activity theory, this paper will analyze those processes of co-design, using a case study as an example, and suggest that teachers recognize and support the role of learners as co-designers. On the one hand, it will contribute to the motivation of the learners. On the other hand, it will improve the quality of the course, adapting it to the needs and wishes of the target group.